Determining CLOU Reaction Kinetics for Combined Oxygen Carriers—Discussing the Experimental Methods. Issue 10 (16th June 2016) - Leion, Henrik; Zhan, Xiang; Frick, Volkmar
Abstract: Combined oxides, primarily manganese based, have shown great potential as oxygen carriers, as they often have oxygen uncoupling properties at relevant temperatures. These oxygen carriers could be a good alternative to copper‐based materials. But in order to scale up or model the chemical‐looping with oxygen uncoupling (CLOU) process reliable oxygen carrier kinetics is needed. The general approach to determine oxygen carrier kinetics is to use thermogravimetric analysis (TGA). However, due to the nature of combined oxygen carriers the conventional approach might not be possible. The objective of this work is to explain and point out the limitations of the conventional way of using TGA for CLOU kinetics. Experiments from three different oxygen carriers, a perovskite, a manganese ore, and a manganese‐silica oxide, are used in order to illustrate the difficulties and spur new thinking in the field. Abstract : Experimental limitations : Thermogravimetric analysis (TGA) is commonly used for determining reaction kinetics in chemical‐looping with oxygen uncoupling. However, this method has some limitations which researchers may not give enough attention. Experiments from three novel oxygen carriers, a perovskite, a manganese ore and a manganese‐silica oxide, are used in order to illustrate relevant difficulties in determining kinetics with TGA.